The cultural adaptation strategies of indigenous populations on the border of East Nusa Tenggara Province-Timor Leste to bureaucracy modernization and development on the country's border are being discussed - Bire Manoe, Lenny Sofia; Nahak, Hildigardis Maria Imaculata; Konradus, Blajan; Peranginangin, Imanta Immanuel (Asean Study Center Lambung Mangkurat University, 2023)
The dynamics that occur in the border region of the country have always been an interesting study to be examined. The government's effort to change the paradigm of the border region is to use a welfare approach, one of which is improving governance in the border region, accelerating development, and equitable development in eastern Indonesia. This effort encountered obstacles and barriers, including the readiness of the community to accept change. In fact, East Nusa Tenggara is a province with a multi-ethnic society, and the people who live in the border area of Province East Nusa Tenggara (NTT) –Timor Leste are indigenous people who are united by strong traditions and have strong emotional ties as a unity of Indigenous Peoples. This study focuses on the cultural adaptation strategies carried out by the indigenous people of NTT in the border areas towards the realization of the Nawacita program (9 national development priorities as the focus of Indonesian renewal in order to have political sovereignty, be able to be independent in managing the economy, and have a cultured personality). The target of this study is to analyze the forms of cultural adaptation of the indigenous people of NTT in adjusting to changes in the border area, along with the inhibiting factors. We use qualitative research methods and data collection techniques through in-depth interviews and FGDs with relevant institutions. The analysis is based on the theories of cultural interaction and cultural adaptation.